Components of leaf‐trait variation along environmental gradients. Issue 1 (24th April 2020) - Dong, Ning; Prentice, Iain Colin; Wright, Ian J.; Evans, Bradley J.; Togashi, Henrique F.; Caddy‐Retalic, Stefan; McInerney, Francesca A.; Sparrow, Ben; Leitch, Emrys; Lowe, Andrew J.
Summary: Leaf area (LA), mass per area (LMA), nitrogen per unit area (Narea ) and the leaf‐internal to ambient CO2 ratio (χ) are fundamental traits for plant functional ecology and vegetation modelling. Here we aimed to assess how their variation, within and between species, tracks environmental gradients. Measurements were made on 705 species from 116 sites within a broad north–south transect from tropical to temperate Australia. Trait responses to environment were quantified using multiple regression; within‐ and between‐species responses were compared using analysis of covariance and trait‐gradient analysis. Leaf area, the leaf economics spectrum (indexed by LMA and Narea ) and χ (from stable carbon isotope ratios) varied almost independently among species. Across sites, however, χ and LA increased with mean growing‐season temperature (mGDD0 ) and decreased with vapour pressure deficit (mVPD0 ) and soil pH. LMA and Narea showed the reverse pattern. Climate responses agreed with expectations based on optimality principles. Within‐species variability contributed < 10% to geographical variation in LA but > 90% for χ, with LMA and Narea intermediate. These findings support the hypothesis that acclimation within individuals, adaptation within species and selection among species combine to create predictable relationships between traits and environment. However, the contribution of acclimation/adaptation vs species selection differs among traits. Abstract : See also the Commentary on this article by Tautenhahn et al ., 228 : 6–10 .